TikTok as an Information Hodgepodge: Evaluation of the Quality and Reliability of Genitourinary Cancers Related Content - Xue, Xiaoqiang; Yang, Xinyi; Xu, Weifeng; Liu, Guanghua; Xie, Yi; Ji, Zhigang (Frontiers in Oncology, 2022)
ABSTRACT Background: TikTok is the world's fastest-growing video application, with 1.6 billion users in 2021. More and more patients are searching for information on genitourinary cancers via TikTok. We aim to evaluate the functional quality and reliability of genitourinary cancer-related videos on it and share our thoughts based on the results for better public health promotion. Materials and Methods: We retrieved 167 videos on bladder, prostate, and kidney cancer from TikTok. Only 61 videos (36.53%) met the inclusion criteria and were eventually regarded as sample videos. Each video's length and descriptions, hashtags, number of views/likes/comments, forms of expression, and the uploader's profile were included. Three validated assessment instruments: the Hexagonal Radar Schema, the Health on the Net Code scale, and the DISCERN instrument, were used for evaluating the quality and reliability of the information. All misinformation was counted and categorized. Univariate analysis of variance was performed for analyzing the results. The Post-Hoc least significant difference test was conducted to explore further explanation. Results: Amongst 61 sample videos, healthcare practitioners contributed the most content (n = 29, 47.54%). However, 22 posts (36.07%) were misinformative, and the most common type was using outdated data. More than half of the videos could provide good (> 1 point) content on the diseases' symptoms and examinations. However, the definition and outcomes were less addressed (tied at 21%). The HONcode scale and the DISCERN instrument revealed a consistent conclusion that most videos (n = 59, 96.72%) on TikTok were of poor to mediocre quality. Videos published by media agencies were statistically better in terms of reliability and overall score (P = 0.003 and 0.008, respectively). Fifty-three videos (86.89%) had at least two unexplained medical terms. Healthcare professionals tend to use professional terms most (mean = 5.28 words). Conclusions: Most videos on genitourinary cancers on TikTok are of poor to medium quality and reliability. However, videos posted by media agencies enjoyed great public attention and interaction. Medical practitioners could improve the video quality by cooperating with media agencies and avoiding unexplained terminologies.